Design, Synthesis and Ring‐Opening Properties of a New Bipyridine Fused Rhodamine‐Like Chelating Ligand and the Related Transition Metal Complexes†. Issue 6 (10th May 2021) - Qian, Zhiyuan; Cheng, Yukun; Zhao, Shunan; Wong, Keith Man‐Chung
Main observation and conclusion: A new bipyridine fused rhodamine‐like chelating ligand and the corresponding transition metal complexes of platinum(II) and iridium(III) have been designed, synthesized and structurally characterized by X‐ray crystallography. Their photophysical properties and acid‐ or metal ion‐promoted spirocarbon ring‐opening properties have been investigated. The platinum(II) and iridium(III) complexes show a drastic color change in solution with Hg 2+ ions and emergency of an absorption band at around 450—600 nm, assignable to the absorption band of the ring‐opened rhodamine‐like ligand. The platinum(II) complex was suggested to undergo dissociation with Hg 2+ ion, based on the corresponding absorption titration study. Emission titration studies of iridium(III) complexes were found to suffer from the quenching process, probably due to the presence of a lower‐lying non‐emissive excited state from the ring‐opened form of ligand. Abstract : A new bipyridine embedded rhodamine‐like chelating ligand with sensory function, together with the related transition metal complexes, have been designed, synthesized and characterized. The corresponding spirocarbon ring‐opening process results in drastic color change and emission perturbation and the corresponding sensing behaviors have been studies by UV‐Vis absorption and emission spectroscopies.